2012
DOI: 10.1093/eurheartj/ehs113
|View full text |Cite
|
Sign up to set email alerts
|

From abstract to impact in cardiovascular research: factors predicting publication and citation

Abstract: AimsThrough a 4-year follow-up of the abstracts submitted to the European Society of Cardiology Congress in 2006, we aimed at identifying factors predicting high-quality research, appraising the quality of the peer review and editorial processes, and thereby revealing potential ways to improve future research, peer review, and editorial work.Methods and resultsAll abstracts submitted in 2006 were assessed for acceptance, presentation format, and average reviewer rating. Accepted and rejected studies were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 26 publications
4
58
3
4
Order By: Relevance
“…However, other authors found no differences in publication percentages between oral and poster forms of presentations (Balasubramanian et al 2006;Rodriguez and Laskin, 2012;Winnik et al, 2012). Presence of statistical analysis was also significantly associated with a favourable publication outcome.…”
Section: Discussionmentioning
confidence: 83%
“…However, other authors found no differences in publication percentages between oral and poster forms of presentations (Balasubramanian et al 2006;Rodriguez and Laskin, 2012;Winnik et al, 2012). Presence of statistical analysis was also significantly associated with a favourable publication outcome.…”
Section: Discussionmentioning
confidence: 83%
“…[16] Other possible reasons included the presence of previous studies with similar study designs and results, preconceived judgement about the rejection by the journals, study results not providing new scientific contributions, and presence of deficits and errors in statistical methodology. [8,17] Although some studies did not find any significant difference between the publication rates of oral and poster presentations, [17][18][19][20] others showed that the publication rate of oral presentations was higher than poster presentations. [8,21,22] In general, well-designed studies with interesting results which have a higher scientific value are selected as oral presentations by the review committee of the abstracts, and these reports mature further with the feedbacks from the audience.…”
Section: Discussionmentioning
confidence: 98%
“…2 Winnik et al conducted and reported a very comprehensive manual study on this same topic using data from ≈1000 randomly selected abstracts from the European Society of Cardiology Scientific Sessions. 3 Their study was published when our manuscript was in the review process for Circulation. The results reported by Winnik et al were similar to ours, although in a smaller sample.…”
Section: Correspondencementioning
confidence: 99%